Thermoluminescence properties of optical fibers doped with RE+3 (RE=Sm, Nd) ions subjected to X-ray irradiation - Refaei, Azadeh (Trans Tech Publications, 2014)
This paper describes the thermoluminescence properties of RE+3(RE=Nd, Sm) doped optical fiber SiO2. The samples were exposed to 6 MV X-ray irradiation at dose ranging from 0.5 to 4 Gy at hospital Sultan Ismail, Johor Bahru, Malaysia using the LINAC accelerator. After exposure and a certain delay of 12 h to get uniform control of thermal fading, the optical fiber TL yield was readout using a thermoluminescence (TL) reader. The optical fiber demonstrated a linear TL response versus of the absorbed dose. The linearity increases with the increasing dose while in the case of Sm-doped optical fiber, the response is comparatively smaller than Nd-doped optical fiber. Also, the glow curve of RE+3 ions doped optical fiber was compared with the undoped fibers. The results exhibit that the glow curve peaks are shifted to higher temperature due to rare-earth doping. The results indicate the TL response strongly depends on the doping type of materials. All these TL characteristics are proposing this commercial optical fiber very decisive TL material.